2023
DOI: 10.1021/acsomega.3c05692
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Evaluation of Highly Inhibitory Oil Well Cement Retarders with Branched-Chain Structures

Bin Lv,
Jingfu Zhang,
Shuai Xie
et al.

Abstract: Cementing at medium temperature and high temperature (90–150 °C) is facing challenges on account of the properties of the retarders. Except for the thermal stability, abnormal gelation, such as “bulging” and “stepping”, often takes place and results in safety problems. In this article, the synthesis of a new retarder DRH-150 was introduced. First, a main chain with thermal-resistant groups, 2-acrylamido-2-methylpropanesulfonic acid-acrylic acid (AMPS-IA-AA) was prepared by free radical polymerization. Second, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Both the laboratory study and field application have found that the AGP of cementing tail slurry at high temperature was prone to occur under a low retarder dosage (usually ≤1.5% bwoc) . Compared with the thickening performance of PAIA retarder in Table , the thickening performances of tail slurry with (a) 0.5% and (b) 1.0% bwoc retarder PAIANS at 120 °C/60 MPa are shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…Both the laboratory study and field application have found that the AGP of cementing tail slurry at high temperature was prone to occur under a low retarder dosage (usually ≤1.5% bwoc) . Compared with the thickening performance of PAIA retarder in Table , the thickening performances of tail slurry with (a) 0.5% and (b) 1.0% bwoc retarder PAIANS at 120 °C/60 MPa are shown in Figure .…”
Section: Resultsmentioning
confidence: 99%